Who benefits from state and local economic development policies? - Bartik, Timothy J. (W.E. Upjohn Institute for Employment Research, 1991)
Examines the impact of state and local economic development policies on employment growth, prices and income distribution. Argues that state and local policies can significantly affect local growth, and that these policies can have a variety of distributional effects, depending on the specific policy and the characteristics of the local economy.